2022
DOI: 10.1007/s00167-022-07001-7
|View full text |Cite
|
Sign up to set email alerts
|

Raised initial total white cell count and lower post-operative decline of C reactive protein increases the risk of secondary surgery in septic arthritis of the native knee

Abstract: PurposeSeptic arthritis is an orthopaedic emergency with high morbidity and mortality. The aim of this study is to determine the risk factors associated with secondary surgery for septic arthritis of the native knee joint. MethodsThis is a retrospective study reviewing all patients who underwent surgery for septic arthritis of the knee from 2012 to 2019 in a single institution. A total of 117 patients were recruited. Patients were divided into 2 groups: Group I (79/117, 67.5%) underwent one surgery and Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Strict inclusion and exclusion criteria were utilised to ensure that included articles were relevant and of suitable scientific standard. We note a potential study for inclusion from Yeo et al [ 48 ] with relevant outcomes, however, given that there is no description for diagnosis of septic arthritis, it was accordingly excluded. Another article by Kerbel et al [ 26 ] reported on our secondary outcomes comparing arthroscopy and arthrotomy and would have been considered for inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Strict inclusion and exclusion criteria were utilised to ensure that included articles were relevant and of suitable scientific standard. We note a potential study for inclusion from Yeo et al [ 48 ] with relevant outcomes, however, given that there is no description for diagnosis of septic arthritis, it was accordingly excluded. Another article by Kerbel et al [ 26 ] reported on our secondary outcomes comparing arthroscopy and arthrotomy and would have been considered for inclusion.…”
Section: Discussionmentioning
confidence: 99%